(untitled) (Economic and Political Thought, 2024)
The aim of this article is a comparative analysis of parties and single-purpose parties in Poland, with particular focus on Self-Defence of the Republic of Poland, the Palikot Movement, Kukiz’15 and Nowoczesna. The author wants to understand the factors of the electoral success of these groupings and the reasons for their decline despite an initial increase in popularity. The analysis covers the dynamics of organisational development and changes in support of these parties, their programmes, political strategies and the role of leaders. The researched article analyses the phenomenon of single-purpose parties in Poland, such as Samoobrona RP, Ruch Palikota, Kukiz’15 and Nowoczesna. The author examines why these parties, despite their initial success, do not last long on the political scene. Single issue parties are a common phenomenon in political systems, including Poland. Although short-lived, groupings such as the Self-Defence of the Republic of Poland and the Palikot Movement have had a significant impact on the political landscape. Studying these parties can help to understand the role of charismatic leaders and populism in society and politics.